(untitled) (Global Journal of Human-Social Science, 2023)
This article analyzes the relationship between the quality of democracy and homicide rates in Latin America Our hypothesis is that governments with authoritarian tendencies in Latin America do not necessarily have higher homicide rates than those without these tendencies Our research focuses analyzing the quality of democracy in four countries Brazil and Colombia categorized as weak democracies and Peru and Bolivia considered hybrid regimes Secondary data obtained from the Economist Intelligence Unit Our World in Data and the World Bank Group websites were used for this analysis Findings indicate that weakening of institutions is an important contributor to homicide rates in weak democracies Brazil and Colombia However this factor has less of an impact on homicide rates in hybrid regime countries Peru and Bolivia where the fragility of democracy coexists with lower homicide rates